Descentralização e endividamento municipal: formas, limites e possibilidades - Gremaud, Amaury Patrick (2009)
The objective of this article is to discuss alternatives to finance investments by municipalities. In general, current revenues are insufficient to finance large investments, what brings about the necessity of municipal indebtedness. These could assume different manners, according to the nature of the investment: if it is typically public or if it offers private return. For the first case, we discuss the possibilities of a municipal bond market and, for the second, we discuss project finance and the participation of the private sector.